Milia-like idiopathic calcinosis cutis of the forehead in an adult without Down's syndrome successfully treated with a CO2 laser (2020)
Background: Idiopathic calcinosis cutis is an uncommon form of calcinosis cutis. It may present as tumoral calcinosis, subepidermal calcified nodules or scrotal calcinosis. Subepidermal calcified nodules may also present as milia-like lesions commonly seen in children with Down's syndrome in the absence of tissue damage or metabolic disorders, it has been seldom reported in adults. The treatment of choice is surgical excision. However, a surgical approach may not always be beneficial to the patient given the cosmetic outcomes. Here, we describe the successful use of a CO2 laser in the treatment of milia-like calcinosis cutis of the forehead in an adult without Down's syndrome. Aims: To describe the treatment of Milia-like idiopathic calcinosis cutis of the forehead in an adult without Down's syndrome successfully treated with a CO2 laser. Methods: We report a case of a 48-year-old man who presented with skin-colored hard asymptomatic papules on the forehead that started about 9 years ago, a biopsy was performed and a diagnosis of milialike calcinosis cutis was made. Surgical excision was discarded regarding the location and the number of lesions, instead, a CO2 laser was used to treat this condition. Results: Successful laser excision of the lesions with appealing cosmetic results. Conclusions: CO2 laser seems to be a valuable tool to treat milia-like calcinosis cutis lesions. © 2019 Wiley Periodicals, Inc.